Economic Empowerment of Dhuafa Families Through Digital Business and Financial Management Based on Maqashid Sharia in Tambakrigadung, Lamongan - Tika Widiastuti; Puji Sucia Sukmaningrum; Lina Nugraha Rani; Muhammad Ubaidillah Al Mustofa; Ninda Ardiani (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
Indonesia has an agricultural sector that contributes signiﬁcantly to the Indonesian economy. However, when the COVID-19 pandemic aﬀected the agricultural industry, it impacted much on the Maju Mulyo Farmer Group in Tambakrigadung, Lamongan. The majority of members of the Maju Mulyo Farmer Group were classiﬁed as dhuafa, which means that they had limitations in developing their businesses, planning family ﬁnances, and in using technology optimally to support business continuity. The solution provided was through community economic empowerment activities related to Maqashid Sharia-based ﬁnancial management and digital marketing. The method began by identifying the existing conditions of the Maju Mulyo Farmer Group. Subsequently, it was proceeded with the training stages which included product development training, business management, recording simple accounting reports, e-commerce, digital marketing, and family ﬁnancial management. The last stage consisted of mentoring, empowering, monitoring, and evaluation. The results of community service activities and providing training with regular assistance could open new insights for rural communities regarding ﬁnancial and business management amid the COVID-19 Pandemic. Financial management and digital business could facilitate the daily activities of residents and improve the ability of villagers to survive during the COVID-19 pandemic.